Physical therapy on the conservative treatment on adolescent with Scheuermann’s Disease – a case report. - Duarte, Rafael Turqueto; Serenza, Felipe; Almeida, Gabriel Peixoto Leão; Kanas, Michel; Gongora, Hélcio (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The Scheuermann’s kyphosis may cause difficulties in social acceptance and in the practice of physical activity in adolescents, mainly caused by deformity of the thoracic spine. This change is diagnosed by radiological imaging when at least three adjacent vertebrae submit a previous larger than 5° wedging. Patients who have a Cobb angle greater than 75° are indicated for surgery. However, to date there is no agreement on how best to approach the patient in the conservative treatment. Objective: To present the conservative treatment of the back pain on an adolescent with Scheuermann’s disease. Method: Case report of a young patient complaining of back pain and with the Cobb angle greater than 75°, treated with exercises and postural reeducation for 12 weeks. The changes on flexibility of the spine was measured by the popliteal angle and with a fio de prumo. Moreover, it was evaluated the isometric strength of the trunk, the functional capacity by the Oswestry questionnare and the pain with a Visual Analogue Scale. Results: The patient improved with his pain and functional abilities, maintaining the practice of exercises by himself at home. Conclusion: After learning the exercises and practice it at home, with the orientation of a manual and the physical therapist, the patient do not presented any more complaining of pain